Composite Cluster as a Factor of Aerospace Brach Development in Perm Krai - ANDREEVA, Olga Yu.; POSTNIKOV, Vladimir P. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
In today’s economy competition is getting severe not only on between companies, but also on the level of territories. This is why clusters in both developed countries and in Russia are becoming the new way of getting competitive advantages through creation of new highly qualified labour options, through innovative entrepreneurship development and closer cooperation of capital and science. The authors of this article carry out the analysis of the already existing clusters from the standpoint of their efficiency and applying the methodology of the European Cluster Observatory as well as several other approaches developed by Russian researchers. As of today the map of clusters for Russian Federation shows a very insignificant number of clusters in the field of new materials and technologies. Thus, this article suggests a structure for an aerospace composite cluster for Perm Krai. This region already has several innovation clusters, and this is why there is already a certain organizational and intellectual potential for this new cluster. During spring 2016 the government of Perm Krai was discussing the decision on this new structural unit – a composite cluster, however, detailed research on its potential structure has not been carried out. Basing on the available demand of the local market and evaluation of the parameters of the already successful industrial and innovation clusters in Russia we suggest here the strategic guidelines for the discussed cluster development until 2020.